1997
DOI: 10.1021/ja970588i
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of Singlet and Triplet Arylnitrenes:  Temperature-Dependent Photodecomposition of 1-(2-Azidophenyl)-3,5-dimethylpyrazole

Abstract: At >200 K photolysis of 1-(2-azidophenyl)-3,5-dimethylpyrazole (5) gives 1,3-dimethylpyrazolobenzotriazole (6, by electrophilic cyclization of singlet nitrene 1 4) or, in the presence of diethylamine, aminoazepine 8 (by addition of the nucleophile and rearrangement). At lower temperatures, the yield of these products decreases and the azo derivative 9 (from the dimerization of triplet nitrene 3 4) as well as products from intramolecular radical cyclization (again via 3 4) is obtained, to become the only produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 25 publications
1
36
0
1
Order By: Relevance
“…It seems that phenylnitrene derivatives mainly decay by dimerization, but there are several reports that they form aniline‐like products 10, 40. Furthermore, Albini et al 52, 53. and Schuster and Schrock54 reported that amino‐substituted phenyl derivatives also form aniline‐like products, but they suggest that these aniline derivatives are more likely to be formed via electron transfer rather than H‐atom abstraction via triplet phenyl nitrenes.…”
Section: Resultsmentioning
confidence: 99%
“…It seems that phenylnitrene derivatives mainly decay by dimerization, but there are several reports that they form aniline‐like products 10, 40. Furthermore, Albini et al 52, 53. and Schuster and Schrock54 reported that amino‐substituted phenyl derivatives also form aniline‐like products, but they suggest that these aniline derivatives are more likely to be formed via electron transfer rather than H‐atom abstraction via triplet phenyl nitrenes.…”
Section: Resultsmentioning
confidence: 99%
“…231~234 , ℃ 棕褐色固体. 1 H NMR (300 MHz, DMSO-d 6 ) δ: 9.15 (s, 1H), 9.01 (d, J=1.5 Hz, 1H), 8.75~8.74 (m, 1H), 8.04 (d, J=8.4 Hz, 1H), 7.94 (d, J=8.4, 1H), 7.33~7.29 (m, 1H), 7.13~7.07 (m, 1H); 13 C NMR (75 MHz, DMSO-d 6 ) δ: 147. 6, 138.3, 129.8, 129.5, 127.3, 125.7, 117.0, 116.8, 116.1, 114.5, 112.5, 108.6. 1,3-二甲基吡咯[1,2-a]喹喔啉(3e) [7] : m.p.…”
Section: Entrymentioning
confidence: 99%
“…1 H NMR (300 MHz, CDCl 3 ) δ: 8.63 (s, 1H), 8.12 (d, J=7.4 Hz, 1H), 7.88 (d,J=7.0 Hz,1H),7.52~ 7.36 (m,2H),6.39 (s,1H), 2.86 (s, 3H), 2.41 (s, 3H); 13 C NMR (75 MHz, CDCl 3 ) δ: 144.2, 137.3, 130.4, 129.7, 128.1, 126.2, 124.7, 124.4, 117.3, 116.9, 115.3, 17.6, 10.2. 1-苯基吡咯[1,2-a]喹喔啉(3f) [7] : 蜡状固体. 1 H NMR (300 MHz, CDCl 3 ) δ: 8.70 (s, 1H), 7.82 (d,J=8.0 Hz,1H), 7.40~7.36 (m, 5H), 7.28 (d,J=8.5 Hz,1H),7.22 (t,J=7.7 Hz, 1H), 6.99 (t, J=8.1 Hz, 1H), 6.83 (d, J=4.0 Hz, 1H), 6.64 (d,J=4.0 Hz,1H); 13 C NMR (75 MHz, CDCl 3 ) δ: 146.1, 137.2, 134.1, 132.4, 130.0, 129.8, 129.1, 128.9, 128.8, 128.7, 128.6, 127.8, 126.4, 125.0, 116.7, 116.6, 107.6. 吲哚[1,2-a]喹喔啉(3g) [7] : m.p. 111~113 , ℃ 橙色固 体.…”
Section: Entrymentioning
confidence: 99%
See 2 more Smart Citations